2006
DOI: 10.1103/physrevlett.97.153903
|View full text |Cite
|
Sign up to set email alerts
|

Two-Color Vector Solitons In Nonlocal Media

Abstract: We investigate the interaction between two beams differing in wavelength and the properties of dual-frequency spatial solitons in nonlocal birefringent reorientational media. We report the first experimental observations of anisotropic nonlocal vector solitons in unbiased nematic liquid crystals. Model and simulations, based on the paraxiality along the Poynting vectors, include joint walk-off and breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 26 publications
1
80
0
Order By: Relevance
“…The latter response provides a low-power mechanism for nonlinear optics [19] and light localization into self-confined lightbeams, the so-called "nematicons" [20]. Nematicons are bright spatial solitons (solitary waves) which are stable in two transverse dimensions due to the nonlocal response associated with the elastic intermolecular links in the liquid state [21,22]; they support graded-index waveguides able to confine additional (incoherent) signals/beams of different wavelengths as well as powers and profiles [23][24][25][26][27][28][29][30], are robust against refractive index perturbations [31][32][33][34][35] and collisional interactions [36][37][38]. Aided by nematicons, reorientational and electronic nonlinear responses, characterized by distinct time-and power-scales, can synergystically be combined [39,40].…”
mentioning
confidence: 99%
“…The latter response provides a low-power mechanism for nonlinear optics [19] and light localization into self-confined lightbeams, the so-called "nematicons" [20]. Nematicons are bright spatial solitons (solitary waves) which are stable in two transverse dimensions due to the nonlocal response associated with the elastic intermolecular links in the liquid state [21,22]; they support graded-index waveguides able to confine additional (incoherent) signals/beams of different wavelengths as well as powers and profiles [23][24][25][26][27][28][29][30], are robust against refractive index perturbations [31][32][33][34][35] and collisional interactions [36][37][38]. Aided by nematicons, reorientational and electronic nonlinear responses, characterized by distinct time-and power-scales, can synergystically be combined [39,40].…”
mentioning
confidence: 99%
“…A novel class of vector solitons in the form of two color spatial solitons in a highly nonlocal and anisotropic Kerr-like medium were predicted to exist in nematic liquid crystals [8][9][10]. The first experimental observations of anisotropic, nonlocal vector solitons in unbiased nematic liquid crystals were reported by Alberucci et al [10], who investigated the interaction between two beams of different wavelengths and observed that two extraordinarily polarized beams of different wavelengths can nonlinearly couple, compensating for the beam walk-off, so creating a vector soliton.The main purpose of this Letter is twofold. Firstly, we introduce a novel class of vector solitons in nonlocal, nonlinear media, such as nematic liquid crystals and study their properties.…”
mentioning
confidence: 99%
“…The nonlocality can suppress the modulation instability [30,31] and transverse instability [32], and prevent the catastrophic collapse of high-dimensional optical beams [33]. Nonlocal nonlinearity also sustains vector coupled solitons, including vector dipole soliton pairs [34,35], multi-pole vector solitons [36,37], two-color vector solitons [38][39][40], bright and dark solitons [41], vector vortex [42] and necklace solitons [43].…”
Section: Introductionmentioning
confidence: 99%